Evaluation of Damage to Existing Buildings Induced by Tunnel Excavation - Ekin Evrim Laçin Akşit; Kadir Güler (Infrastructures)
This study emphasizes the significance of employing systematic approaches and precise modeling techniques to evaluate potential building damage from metro tunnel excavations. Mair et al. (1996) proposed a three-stage assessment framework comprising preliminary assessment, second-stage assessment, and detailed assessment to analyze the damage to buildings inflicted by tunnel excavation. For preliminary and second-stage assessments, parametric calculation methods have been examined; however, detailed assessment requires using a 3D numerical analysis model. This study selected a school building, to examine this three-stage assessment method. For the preliminary and second stage assessments, a “greenfield” analysis approach was utilized using the PLAXIS 2D to determine the ground settlement curve caused by tunnel excavation. Based on the obtained settlement values, the evaluation was conducted using the boundary conditions proposed by Mair et al. (1996). Since the obtained settlement values did not meet the proposed boundary conditions, a three-dimensional finite element model was generated using the SAP2000 analysis program. This paper offers practical guidance on the nonlinear modeling principles of structural elements during the detailed assessment of a building subjected to vertical settlement. It provides a framework for assessing buildings near tunnel construction sites.